Selection index by final and weaning weight in buffalo performance tests in Cuba - Fraga, L.M.; López, O.; García, Yenny (Cuban Journal of Agricultural Science, 2024)
Performance tests were carried out on 241 male buffaloes from the Empresa Pecuaria Genética Los Naranjos, in Cuba, during the years 2011/2012 and 2017. The evaluated indicators were weight at weaning at eight months, final weight at 20 months of age, weight gain from eight to 20 months, weight per age at 20 months and milk production of their mothers at 244 days, as well as the percentage values, calculated from their respective annual means. A mixed model was used (Proc Glimmix of SAS 2013), which considered the year of entry into testing as a fixed effect, and the individual nested in the year of entry as random effect. The genetic values (GV) with their precision were estimated using a two-character model, compiled in IML (Interactive Matrix Language) of SAS. This considered genealogy (250 males and females), which, together with the 241 observations of tested animals, formed a kinship matrix of 491 individuals. Weaning (136.43 and 151.92 kg) and final (285.39 and 333.35 kg) weights were low, while the production of their mothers was acceptable (944.04 and 1,135.42 kg). It is concluded that the selection index, constructed from the variances and covariances of phenotypic and genetic values, economically weighted as a regression of the observed deviations from their means of weaning and final weight, is a reliable method for the selection of buffaloes in performance tests.